Entomopathogenic nematode food web assemblages in Florida natural areas. (February 2016) - Campos-Herrera, Raquel; El-Borai, Fahiem E.; Rodríguez Martín, Jose Antonio; Duncan, Larry W.
Abstract: In Florida citrus orchards, root weevil herbivory is tempered by four native entomopathogenic nematode (EPN) species whose spatial patterns are associated with soil properties related to water content. Manipulation of these variables could affect the efficacy and conservation of native EPNs for control of root weevils. The diversity of EPNs in non-agricultural areas it is unknown. We speculated that, whereas different species composition may occur in some natural areas by virtue of non-citrus niche adaptations, similar soil properties and environmental conditions should shape the communities in both systems. We characterized EPN food web assemblages during summer-fall 2011 in 91 sites comprising five naturally occurring botanical groups (oak, pine, palm and palmetto, mixed and other) and two ecoregions (central ridge and flatwoods). We used species-specific qPCR probes for 13 EPN species, two species of Paenibacillus (ectoparasitically associated with EPNs), seven species of nematophagous fungi (NF), an oomycete pathogen of citrus ( Phytophthora nicotianae ) and free-living bactivorous nematodes ( Acrobeloides -group), some of which compete with EPNs. Seven EPN species were detected at frequencies about 60% of that reported from citrus. Additional species detected were Steinernema glaseri and Heterorhabditis floridensis, whereas citrus inhabitants Steinernema riobrave and Steinernema scapterisci, were absent, suggesting a possible niche adaptation. EPN recovery frequency did not differ between two ecoregions, except for Heterorhabditis indica which was detected at more sites in the flatwoods than on the central ridge and Heterorhabditis zealandica exhibiting the opposite pattern for detection frequency and abundance. Nor did the botanical habitats much affect EPNs other than H . indica which occurred with greatest frequency and abundance in abandoned citrus orchards. Soil moisture appeared to be important in modulating these subterranean communities, with groundwater depth, organic matter, soil clay and pH explaining significant EPN variability between sites. There was little evidence that regional or habitat differences in natural enemy occurrence affected the EPN spatial patterns. Indeed, numerous significant direct associations between species of nematodes and nematophagous fungi suggested that the local abundance of the r-selected EPN and Acrobeloides -group nematodes is an important resource modulating population growth of these trapping and endoparasitic fungi. Congruent relationships between EPN spatial patterns and soil properties that affect water potential in both natural areas and citrus orchards suggests that soil moisture drives these patterns and modulates the regulation of root herbivores by EPNs in this part of the Florida peninsula. Consequently, management of soil moisture by manipulating these properties has the greatest potential to enhance and conserve EPN services. Graphical abstract: Highlights: Entomopathogenic nematodes (EPNs) less abundant in natural areas than citrus. Edaphic properties, not vegetation, predicted EPN spatial patterns. EPNs and bactivorous nematodes predicted nematophagous fungi patterns. Soil properties affecting moisture predicted EPN species occurrence. Manipulation of these properties might conserve or enhance EPN services.